2016
DOI: 10.3389/fpsyt.2016.00189
|View full text |Cite
|
Sign up to set email alerts
|

Altered Insular Function during Aberrant Salience Processing in Relation to the Severity of Psychotic Symptoms

Abstract: There is strong evidence for abnormal salience processing in patients with psychotic experiences. In particular, there are indications that the degree of aberrant salience processing increases with the severity of positive symptoms. The aim of the present study was to elucidate this relationship by means of brain imaging. Functional magnetic resonance imaging was acquired to assess hemodynamic responses during the Salience Attribution Test, a paradigm for reaction time that measures aberrant salience to irrele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 83 publications
2
25
0
Order By: Relevance
“…At a more general level, the impaired neural reward adaptation in the striatum and insula is in line with a general deficit in basic information processing and with studies showing aberrant salience processing in individuals at risk for psychosis and early disease stages (Manoliu et al, 2014;Smieskova et al, 2015;Walter et al, 2016;Winton-Brown et al, 2017). Specifically, the imprecise neural representation of reward information could lead to increased uncertainty about external stimuli or internal values.…”
Section: Implications For Dysfunctional Reward and Salience Processingsupporting
confidence: 65%
“…At a more general level, the impaired neural reward adaptation in the striatum and insula is in line with a general deficit in basic information processing and with studies showing aberrant salience processing in individuals at risk for psychosis and early disease stages (Manoliu et al, 2014;Smieskova et al, 2015;Walter et al, 2016;Winton-Brown et al, 2017). Specifically, the imprecise neural representation of reward information could lead to increased uncertainty about external stimuli or internal values.…”
Section: Implications For Dysfunctional Reward and Salience Processingsupporting
confidence: 65%
“…The salience network (insular cortex, parietal cortex, and striatum), shown in Figure 3, has been implicated in a function known as the salience monitoring and processing. Salience is defined as the effectiveness of a stimulus to stand out from its neighbors [7]. A stimulus might be considered to be salient by feature contrast, novelty, emotional, or motivational association.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, decreased connectivity within neural systems involved in emotion processing and hyperconnectivity between the emotion system (AN) and the salience processing system (VAN) may relate to the deficits in emotion perception and regulation. Circles refer to reduced connectivity within the corresponding networks [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DMN deactivates during conscious attentional shift to environmental-related stimuli, re ecting introspective, self-relevant processes and affective decisions [28,29]. The SN consists of the insular cortex, parietal ACC, striatum, and limbic structures [30,31], which may be a transitional network that links cognition and emotion/interoception [32]. Previous neuroimaging studies indicated that DMN and SN activity are related to self-relevant processes and attention to internal and external stimuli, including nociceptive input [33][34][35].…”
Section: Discussionmentioning
confidence: 99%